Compatible bedfellows: Enriching grammar pedagogical tasks with cognitive linguistics to teach present simple vs. progressive - Mojtaba Maghsoudi; Abolfazl Khodamoradi (نشریه پژوهش‌های زبان‌شناسی)
While many English language learning textbooks provide exercises on the difference between present simple and present progressive tenses, they often lack meticulous explanations regarding their meaning and contextual usage. Having been inspired by cognitive linguistic studies on English present tense and the theory of Cognitive Grammar, an empirical study was devised to incorporate the elements of cognitive linguistics analysis of English present progressive tense into EFL grammar teaching material. This quasi-experimental study included 53 adult EFL learners being homogenized in terms of their English proficiency based on their scores on Quick Oxford Placement Test, and randomly assigned to three groups. The course of instruction lasted for three weeks during which the groups met 6 times. The cognitive group (N = 18) received cognitive linguistic explanations followed by examples indicating inherited epistemic contingency in English present progressive tense (including, current ongoingness, historical present progressive, future present progressive, temporary validity, duration, iteration, repetition, and modality) and structural construal indicated by present simple. The task-based group (N = 16) received conscious-raising tasks lacking cognitive linguistic explanations. The control group (N = 19) did not receive any explicit instruction. Pretest and posttest scores were used to measure the effectiveness of the types of instruction. The results of paired samples t-test and one-way ANOVA revealed that the cognitive group outperformed the task-based group and the control group showing a higher level of construing usage context of present simple and present progressive tense.